Application of the Electron Density Correlation Function for Structural Analysis of X-ray Scattering/Diffraction Information from Polymer-based Nano-Composites. Issue 1754 (2015) - Song, Kenan; Zhang, Yiying; Tajaddod, Navid; Minus, Marilyn L.
ABSTRACT: Modern diffraction and scattering methods of X-ray radiation allow for multi-scale probing of the material morphology for both polymer-based composite films and fibers. These approaches and analyses tools can be used to map the makeup of individual grain structures in various polymer nano-composites in order to examine the effects of the fillers on nano-scale structural changes in the materials. The electron intensity correlation function, derived from Fourier transformations of the X-ray scattering pattern provides a path to analyze acquired data for space resolved domains. Here in this study, polymer-based nano-carbon composite systems are analyzed. The polymers used include polyvinyl alcohol, polyethylene, and polyacrilonitrile as matrix materials. The nano-carbon filler contribution to the grain size evolution is tracked by X-ray scattering/diffraction characterization. These results show that the relevant sizes of crystalline and amorphous domains within the lamellae structures correspond to the dispersion/distribution of the nano-filler in the composite materials. This work mainly illustrates an effective use of the correlation function to provide global morphological analysis in the composite system.